2001
DOI: 10.1007/s002480000081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inoculation with PGPR Bacillus and Pisolithus tinctorius on Pinus pinea L. growth, bacterial rhizosphere colonization, and mycorrhizal infection

Abstract: The effect of co-inoculation with Pisolithus tinctorius and a PGPR belonging to the genus Bacillus (Bacillus licheniformis CECT 5106 and Bacillus pumilus CECT 5105) in enhancing growth of Pinus pinea plants and the changes that occurred in rhizosphere microbial communities and the degree of mycorrhization were evaluated. Both bacterial strains of Bacillus promote the growth of Pinus pinea seedlings, but this biological effect does not imply a synergic effect with mycorrhizal infection. However, the positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 3 publications
2
39
1
3
Order By: Relevance
“…We acknowledge that soil-assisted strategies are not always economically feasible and complicate infrastructure. Thus we are further exploring the potential roles of other previously reported PGP Bacillus spp., such as B. subtilis [40], B. amyloliquefaciens [41], B. pumilus [10], B. licheniformis [42], and B. megaterium [43], plus other autochthonous bacterial species, alone or together with re-vegetation, in bioremediation of lignite mine waste.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that soil-assisted strategies are not always economically feasible and complicate infrastructure. Thus we are further exploring the potential roles of other previously reported PGP Bacillus spp., such as B. subtilis [40], B. amyloliquefaciens [41], B. pumilus [10], B. licheniformis [42], and B. megaterium [43], plus other autochthonous bacterial species, alone or together with re-vegetation, in bioremediation of lignite mine waste.…”
Section: Discussionmentioning
confidence: 99%
“…Probanza et al (2001) inocularon plantas de Pinus pinea con el hongo ectomicorrícico Pisolithus tinctorius y bacterias del género Bacillus (B. licheniformis y B. pumilus). Ambas bacterias promovían el crecimiento de Pinus pinea sin ningún efecto sinérgico con la micorrización.…”
Section: Micorrización Controlada En Viverounclassified
“…Several authors reported that soil amendment with ectomycorrhizal fungi and plant-growth-promoting rhizobacteria (PGPR) increased plant survival and seedling quality, especially in soils with low microbial activity (Chanway 1997, Probanza et al 2001.…”
Section: Introductionmentioning
confidence: 99%